2016
DOI: 10.1007/s00253-016-8038-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of an F420-dependent glucose-6-phosphate dehydrogenase (Rh-FGD1) from Rhodococcus jostii RHA1

Abstract: Cofactor F420, a 5-deazaflavin involved in obligatory hydride transfer, is widely distributed among archaeal methanogens and actinomycetes. Owing to the low redox potential of the cofactor, F420-dependent enzymes play a pivotal role in central catabolic pathways and xenobiotic degradation processes in these organisms. A physiologically essential deazaflavoenzyme is the F420-dependent glucose-6-phosphate dehydrogenase (FGD), which catalyzes the reaction F420 + glucose-6-phosphate → F420H2 + 6-phospho-gluconolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 65 publications
(104 reference statements)
0
55
0
Order By: Relevance
“…IS2 contains two antiparallel β-strands, and IS3 contains a helical bundle at the C-terminus of the β-barrel and contains the remainder of the substrate-binding pocket ( Figure 3). All structures solved to date from the LLHT family contain a non-prolyl cis peptide in β3 [23][24][25][26]. Recent phylogenetic reconstructions have shown that the F 420 -dependent LLHTs form two clades: the F 420 -dependent reductases and the F 420 -depented dehydrogenases [27].…”
Section: The Llht Familymentioning
confidence: 99%
See 4 more Smart Citations
“…IS2 contains two antiparallel β-strands, and IS3 contains a helical bundle at the C-terminus of the β-barrel and contains the remainder of the substrate-binding pocket ( Figure 3). All structures solved to date from the LLHT family contain a non-prolyl cis peptide in β3 [23][24][25][26]. Recent phylogenetic reconstructions have shown that the F 420 -dependent LLHTs form two clades: the F 420 -dependent reductases and the F 420 -depented dehydrogenases [27].…”
Section: The Llht Familymentioning
confidence: 99%
“…The second contains the F 420 -dependent glucose-6-phosphate dehydrogenases (FGDs) from Mycobacteria and Rhodococcus, while the third appear to be more general sugar-phosphate dehydrogenases [27]. In contrast to the heterodimeric structure of bacterial luciferase, the F 420 -dependent dehydrogenases form homodimers with the dimer interface burying a relatively large portion of the surface area of the monomers (≈2000 Å 2 , roughly 15% Catalysts 2019, 9, 868 5 of 18 of the total surface area) [24][25][26]. A number of enzymes involved in the F 420 -dependent degradation of nitroaromatic explosives, such as picrate and 2,4-dinitroanisole, appear to belong to the LLHT family as well [32,33].…”
Section: The Llht Familymentioning
confidence: 99%
See 3 more Smart Citations